Penta-MS2 (M = Mn, Ni, Cu/Ag and Zn/Cd) monolayers with negative Poisson's ratios and tunable bandgaps as water-splitting photocatalysts. Issue 11 (22nd February 2021) - Lv, Xiaodong; Yu, Linke; Li, Fengyu; Gong, Jian; He, Yong; Chen, Zhongfang
Abstract : Seeking novel materials with specific applications is always an attractive theme in developing two-dimensional (2D) materials. Here 10 2D pentagonal transition metal dichalcogenids are identified with high stability and their promising applications. Abstract : Seeking novel materials with specific applications is always an attractive theme in developing two-dimensional (2D) materials. Herein, we predicted a series of 2D pentagonal transition metal dichalcogenides, namely penta-MS2 (M = Mn, Ni, Cu/Ag and Zn/Cd) monolayers with α and β configurations, by means of systematic density functional theory (DFT) computations. Six α-MS2 monolayers (M = Mn, Ni, Cu/Ag and Zn/Cd) and four β-MS2 monolayers (M = Ni, Ag, Zn and Cd) were found to have sound thermodynamic, dynamic, thermal, and mechanical stabilities, and the coexistence of covalent and ionic bonding contributes to the structural stability of the pentagonal frameworks. All these 10 stable monolayers have low in-plane Young's moduli (8–94 N m −1 ), among which pentagonal β-MS2 (M = Ni, Zn and Cd) monolayers have negative Poisson's ratios (NPRs). Three monolayers (α-CuS2, α-AgS2, and β-AgS2 ) are metallic, and seven penta-MS2 monolayers (M = Ni, Zn and Cd with both α- and β-phases, and α-MnS2 ) are semiconducting with band gaps in the range of 2.45–3.32 eV, and these band gaps can be tuned to 1.70–3.05 eV under rather feasible external strains (−8% to 8%). Notably, two monolayers, namely, α-NiS2 and β-ZnS2, are promising candidates for the photocatalysis of water splitting under neutral conditions. This work not only predicted 10 new 2D pentagonal transition metal dichalcogenides as synthesis targets, but also identified their promising applications for flexible nanomechanics, nanoelectronics and photocatalysis for water-splitting.